Alumina-promoted oxodefluorination - Akhmetov, Vladimir; Feofanov, Mikhail; Amsharov, Konstantin (RSC Advances, 2020)
A simple protocol for the clean preparation of heterocyclic compounds containing dibenzofuran's core via oxodefluorination of fluoroarenes on activated γ-Al2O3 is reported. Alumina can be considered as a reliable oxygen source enabling one-pot substitution of fluorine atoms and yielding benzoannulated furan derivatives. The corresponding C-F bond activation is selective towards less stable C-Br/C-I and occurs under metal- A nd solvent-free conditions.
CRIS-Team Scopus Importer:2020-03-31